Alexander Neill’s «Summerhill» School as an Example of Successful Extrapolation of Psychoanalytic Theory into Pedagogical Practice - Anton Vertel (Pedagogical Discourse, 2023)
The article explicates the experience of successful extrapolation of psychoanalytic theory into pedagogical practice using the example of Alexander Neill’s «Summerhill» free education school. It is argued that the basis of A. Neill’s concept of education are psychoanalytical concepts, namely: classical psychoanalysis of S. Freud, individual psychology of A. Adler, character analysis and body-oriented therapy of W. Reich, humanistic psychoanalysis of E. Fromm. It was established that A. Neill managed to integrate the leading humanistic ideas of the psychoanalytic movement, enriching pedagogical theory and practice and expanding the influence of psychoanalysis on interdisciplinary research. The main principles of A. Neill’s educational system, its general (basic) and special characteristics are clarified.The article traces A. Neill’s pedagogical progress, the evolution of his ideas from the first free education schools «Hellerau» in Dresden to the world-famous «Summerhill» school. Special attention is focused on the peculiarities of the activity of the «Summerhill» school. The organizational foundations of school functioning; approximate daily/weekly schedule; the basic principles of the education system at school; the organizational structure; the role of a teacher in the school education system; peculiarities of the educational process; positive results and achievements of the school education system, contradictions in the «Summerhill» school education system and its criticism are demonstrated.It has been proved that the essence of A. Neill’s concept of free education consists in giving children the freedom of emotional development, the right to independent organization of their lives, the possibility of natural development, ensuring a happy childhood by eliminating fear and pressure from adults. It is shown that the «Summerhill» school represents an interesting and innovative model of the organization of education and upbringing, which is based on the principles of freedom and self-governance and has its advantages and disadvantages, which require further research and discussion.